Evaluation of the Synthetic Scope and the Reaction Pathways of Proton‐Coupled Electron Transfer with Redox‐Active Guanidines in C−H Activation Processes. Issue 69 (3rd November 2020) - Wild, Ute; Walter, Petra; Hübner, Olaf; Kaifer, Elisabeth; Himmel, Hans‐Jörg
Abstract: Proton‐coupled electron transfer (PCET) is currently intensively studied because of its importance in synthetic chemistry and biology. In recent years it was shown that redox‐active guanidines are capable PCET reagents for the selective oxidation of organic molecules. In this work, the scope of their PCET reactivity regarding reactions that involve C−H activation is explored and kinetic studies carried out to disclose the reaction mechanisms. Organic molecules with potential up to 1.2 V vs. ferrocenium/ferrocene are efficiently oxidized. Reactions are initiated by electron transfer, followed by slow proton transfer from an electron‐transfer equilibrium. Abstract : There's a good PECT ! Redox‐active guanidines are used in proton‐coupled electron transfer (PCET) reactions that involve C−H bond cleavage. The study reveals the scope and the mechanism of PCET reactions with and without addition of a strong acid. Substrates with potentials of up to 1.2 V versus ferrocenium/ferrocene could be oxidized in stepwise PCET processes initiated by electron transfer. Experiments with guanidine derivatives show the possibility of tuning the PCET reactivity.